Return to the Pre-Injury Level of Sport after Anterior Cruciate Ligament Reconstruction: A Practical Review with Medical Recommendations - Solie, Braidy S.; Tollefson, Luke V.; Doney, Christopher P.; O'Keefe, Jeremy M. J.; Thompson, Will C.; LaPrade, Robert F. (International Journal of Sports Medicine, 2024)
Returning to sport after anterior cruciate ligament reconstruction (ACLR) can be a challenging and complex process for the athlete, with the rate of return to the pre-injury level of sport observed to be less than athlete expectations. Of the athletes that do return to sport (RTS), knee re-injury rates remain high, and multiple studies have observed impaired athletic performance upon RTS after ACLR as well as reduced playing time, productivity, and career lengths. To mitigate re-injury and improve RTS outcomes, multiple RTS after ACLR consensus statements/clinical practice guidelines have recommended objective RTS testing criteria to be met prior to medical clearance for unrestricted sports participation. While the achievement of RTS testing criteria can improve RTS rates after ACLR, current criteria do not appear valid for predicting safe RTS. Therefore, there is a need to review the various factors related to the successful return to the pre-injury level of sport after ACLR, clarify the utility of objective performance testing and RTS criteria, further discuss safe RTS decision-making as well as present strategies to reduce the risk of ACL injury/re-injury upon RTS. This article provides a practical review of the current RTS after ACLR literature, as well as makes medical recommendations for rehabilitation and RTS decision-making after ACLR.
Keywords: ACLR; rehabilitation; performance testing; pre-injury level of sport; psychological readiness; return to sport